Sabellariids (Annelida: Sedentaria: Sabellariidae) from shallow waters of the Gulf of Mexico and the Caribbean Sea, including three new species - Chávez-López, Yessica (Zootaxa, 2021)
The Sabellariidae has been scarcely studied in the Gulf of Mexico and the Caribbean Sea, and there are 18 species recorded out of 140 species known in the world. This work aims to improve the knowledge of the sabellariids in the northwestern tropical Atlantic region, provide standardized descriptions, and generate taxonomic identification keys. Sabellariids from three scientific collections were revised: Reference Collection of Laboratorio de Poliquetos, El Colegio de la Frontera Sur (ECOSUR), Chetumal, Collection of Laboratorio de Biodiversidad y Cambio Climático, ECOSUR, Campeche and Invertebrate Zoology Collection of Florida Natural History Museum, University of Florida, Gainesville. Three new species are described: Idanthyrsus bastidai n. sp. and I. mikeli n. sp. from Venezuela, and Sabellaria salazari n. sp. from the Yucatán Peninsula. In addition, new records of S. floridensis Hartman, 1944, S. vulgaris Verrill, 1873, and Phragmatopoma caudata Krøyer in Mörch, 1863 are provided.